THE ROLE OF SCOUT EXTRACURRICULAR ACTIVITIES IN SUPPORTING ISLAMIC RELIGIOUS EDUCATION LEARNING BASED ON THE MERDEKA CURRICULUM AT SMP NEGERI 1 PAJAR BULAN - Agustiawan, Bobi; Hadi, Supian (FAJAR Jurnal Pendidikan Islam, 2025)
This study aimed to explore the role of Scout extracurricular activities in supporting Islamic Religious Education (IRE) learning based on the Merdeka Curriculum at SMP Negeri 1 Pajar Bulan. The research employed a qualitative descriptive approach, with data collected through interviews, observations, and documentation. The findings indicated that Scout activities at the school were implemented in a structured and effective manner. These activities not only fostered students' character development but also enhanced their understanding and application of Islamic teachings in daily life. Adequate facilities, such as designated activity spaces, training equipment, and well-organized administration, contributed to the program's success. Students who actively participated in Scout activities demonstrated positive character growth aligned with the values of Islamic Religious Education. Therefore, Scout extracurricular activities played a significant role in supporting the achievement of IRE learning objectives within the Merdeka Curriculum framework.